A comparative study of Ligation of Intesphincteric Fistula Tract versus conventional fistulectomy in management of low fistula in ano: a randomized control trial - Goudar, Bhimanagouda V.; Dakhani, Nawaz M. (International Surgery Journal, 2020)
Background: Fistula in ano (FIA) is a chronic complex condition of ano-rectal sepsis characterized by cylical-pain and intermittent chronic purulent discharge. The management of fistula is challenging. In spite of all the advances in the management of FIA, no single method is univresally applicable to all types of FIA due to incontinence and recurrences associated with the individual procedures. Methods: Aims of this study were to compare the outcomes between ligation of intersphincteric fistula tract (LIFT) and conventional fistulectomy (CF) with 60 patients randomized into 2 groups, 30 in each group. Results: Mean age in LIFT was 44.17 years and in CF was 41.1 years. Successful primary healing was observed in 86.7% of LIFT and 100% of CF. Mean pain scores were lower in LIFT compared to CF when checked on Postoperative days 1, 3 and 7 significantly. Anal incontinence was seen in 10% of CF and none in LIFT and recurrence was seen at same site in LIFT in 6.66% of LIFT and none in CF both being not statistically significant. Conclusions: LIFT is a promising and sphincter saving technique which is simple and easy to learn with faster healing rates and better patient contentment but with risk of failure and recurrence. Modifications of LIFT have to be probed for minimizing the failures.